The Fate of Nitrogen and Faecal Coliform in the Lubigi Wetland in Uganda - Kayima, John K.; Mayo, Aloyce W.; Nobert, Joel K. (Tanzania Journal of Engineering and Technology, 2019)
The capacity of the Lubigi wetland to reduce nitrogen and faecal coliform pollution entering Lake Kyoga in Uganda was investigated. Three transects with 5 sampling points in each, were established in the wetland. Wetland plants samples were collected from the specific locations along the transects, and laboratory tests and analyses were carried out for plants biomass and nitrogen contents determination. Samples of wetland sediments were also collected, and laboratory tests and analyses were done for determination of nitrogen content in the sediments. Wetland water samples were taken from the main wetland inlet and the main outlet from the wetland main study area. At the same time, wetland water pH, dissolved oxygen and temperatures were measured in-situ. Laboratory tests and analyses for ammonia-nitrogen, nitrate-nitrogen, total Kjeldahl nitrogen, total nitrogen and faecal coliforms were carried out on the wetland water samples. The results indicate that the Lubigi wetland received about 16 to 173 mg/l of total nitrogen, largely in form of organic- nitrogen (64.7%) and ammonia-nitrogen (35.2%). Nitrate-nitrogen and Nitrite-nitrite accounted for only 0.1% of the total nitrogen in the inlet. The wetland removed about 24.9% of this nitrogen, which is equivalent to removal of about 1,672 tons of nitrogen annually. About 67.5 gN/m2 and 0.30 gN/kg of dry sediments were sequestered in the wetland plants biomass and the benthic layer respectively. The Lubigi wetland main study area also receives faecal coliform concentrations with the wetland inlet mean value of 653,509 CFU/100ml and its outlet mean value is 218,676 CFU/100ml. These values give a faecal coliform (FC) overall removal efficiency of approximately 66.5%. It was thus concluded that the Lubigi wetland has considerable capacity to buffer and protect Lake Kyoga, by reducing nitrogen and faecal coliform pollution entering the lake. Key words: Faecal coliform pollution, Lubigi wetland, Nitrogen removal.